(untitled) (Management & Public Policies Journal, 2018)
The article presents results of a research done on social representations of violence and types of violence produced by different social sectors in the district of Itaquera, in São Paulo City. The main objective of the study was to identify possible differences in the social representations of violence and types of violence emerging from different social segments. The study was based on the theory of Social Representations by Serge Moscovici and identified important differences among the groups. The conceptof Human Security by Amatya Sen was used as an alternative to face the phenomenon of violence. Focus groups were to collect data.